Small garden animals - Jennings, Terry (New York : Oxford University Press, 1989)
Describes invertebrate animals which can be found in gardens, including insects, spiders, snails, and worms. Includes review questions and related projects
Keywords: Garden animals -- Juvenile literature; Garden animals